Menyingkap makna ayat ayat tasbih dalam surah al baqarah: kajian studi ilmu balaghoh - Syahrullah, Rahmat makruf (Maliki Interdisciplinary Journal, 2025)
This study examines tasybih, which is a style of simile in the science of balaghah, which has an important role in clarifying and beautifying the meaning of Qur’anic verses. Tasybih is used to compare two things that have certain characteristics in common, so that abstract concepts can be conveyed in a more concrete and understandable way. This study focuses on eight verses in Surah Al-Baqarah (verses 17, 19, 74, 93, 146,) that contain different types of tasybih. The analysis shows that tasybih in these verses not only functions as an ornament of language, but also as an effective pedagogical tool to convey moral and spiritual messages, such as hypocrisy, hardness of heart, faith, and obedience. This study identifies four main elements in tasybih, namely musyabbah, musyabbah bih, wajh al-syabah, and adat al-tasybih, and classifies them into nine types, each of which has a specific rhetorical function. By using a textual analysis approach based on classical balaghah theory and contemporary tafsir, it is found that the use of tasybih in the Qur’an is very contextual and structured. .